Equilibrium studies on batch adsorption of alizarin red in aqueous solution using activated carbons derived from orange peels - A.M. Lawal; A. Muhammad (Journal of Applied Sciences and Environmental Management, 2019)
Adsorption has been one of the most preferred methods for the removal of dyes from aqueous solutions due to its simplicity and economic advantages. In this research, activated carbon prepared from orange peels has been characterized using Boehm titration which revealed the surface as having 7.70 mmol/g and 3.64 mmol/g total acidic and basic sites respectively. Scanning Electron Microscope (SEM) imaging showed that the adsorbent had heterogeneous surface morphology while the pH of zero point charge (pHzpc) of the adsorbent was found to be 3.6. Furthermore, Sear’s titration has shown that the activated carbon specific surface area was 791.1 m2 g - . 1The influence of various experimental parameters have been probed and optimized. The optimized conditions were set for the study of adsorption equilibrium and the experimental data were treated using Langmuir, Freundlich, Dubnin-Radushkevic (D-R) and Halsey isotherm models. However, all the four isotherm models were in good fit with the data obtained as indicated by the regression coefficients (R2 value) of 0.944 for the Langmuir isotherm, 0.993 for both Freundlich and Halsey models, and 0.980 for D-R model. The maximum monolayer coverage capacity (qm) was determined to be 11.5 mg/g at room temperature, which is higher than some presented in the previous literature.